Influence of vesicular-arbuscular mycorrhizal fungi sources and levels of phosphorus on the growth of oat forage - Costa, Newton de Lucena; Dionísio, Jair Alves; Anghinoni, Ibamor (Pesquisa Agropecuaria Brasileira, 2014)
The effects of vesicular-arbuscular mycorrhizae (VAM), sources (Triple superphosphate and Patos de minas rock phosphate) and phosphorus levels (0, 30 and 60 kg of P2O5/ha), on dry matter yield, concentration and P uptake by oat forage species (black oat - Avena strigosa Schereb. cv . Comum and yellow oat - A. byzantina Koch. cv. Coronado) - were evaluated in a greenhouse trial at Faculty of Agronomy - UFRGS -, utilizing a Hydromorphic Lateritic soil, sterilized at 110°C for one hour for three days, and reinoculated with a soil microbial suspension free of mycorrhizal fungi spores. An additional treatment with nonsterilized soil and without phosphate fertilization and mycorrhizal inoculation was used. The inoculation of VAM promoved a significative increment (P<0.05) on the DM yield, concentration and P uptake by oat species. The mycorrhizal effects were improved by the phosphate fertilization. The best results were observed with the application of triple superphosphate on the level 60 kg of P2O5/ha. G. macrocarpum was more efficient than native VAM fungi. The yellow oat showed the greatest RMD, independently of P source. The root colonization and the number of spores were increased by the VAM inoculation, mainly with yellow oat cultivation. The P application affected negatively these parameters, at the highest level (60kg of P2O5/ha). The inverse was observed with application of rock phosphate.